Everyday life during the childhood cancer trajectory—childhood cancer survivors' descriptions of the role of caring support - Stenmarker, Margaretha; Björk, Maria; Golsäter, Marie; Enskär, Karin (Frontiers in Rehabilitation Sciences, 2023)
Background Being diagnosed with cancer in childhood often has a direct impact on the child's opportunities to participate in activities and the child's sense of belonging in different life situations. Experiences of illness in youth affect the lives of these individuals in numerous ways and they need pronounced support to regain their normal life after treatment. Purpose To illustrate how childhood cancer survivors describe the role of the caring support provided by healthcare professionals at diagnosis and during the cancer trajectory. Methods A mixed methods approach was applied. Swanson's Theory of Caring was used to deductively analyze the answers in a study-specific questionnaire with Likert scales (1–5). Descriptive and comparative statistics and exploratory factor analyses were performed. Results Sixty-two former patients, diagnosed with solid tumors/lymphoma in 1983 to 2003 in Sweden, participated. The mean time passed since treatment was 15.7 years. Swanson's caring processes Being with and Doing for were the most prominent loading categorical factor indicators. Higher scores for healthcare professionals being emotionally present (Being with), doing for others what they would do for themselves (Doing for) and being willing to understand the sick child's situation (Knowing) were highlighted by survivors older than 30 years, compared to those younger than 30 years (p = 0.041, p = 0.045, and p = 0.013, respectively). An increased vulnerability regarding their ability to cope with difficulties (Maintain belief) was found among participants who were treated during adolescence, related to schoolchildren (p = 0.048), and among those who had been treated with extra-cranial irradiation in comparison with no extra-cranial irradiation (p = 0.004). The role of having a partner in comparison with being single was underlined among those who felt they had acquired the tools they needed to take care of themselves (Enabling) (p = 0.013). The total explained variance was 63%. Conclusions A person-centered care approach during treatment for childhood cancer, reflected by a caring model, highlights the role of healthcare professionals being emotionally present, involving children, performing actions, and with an approach that has potential long-term implications. Childhood cancer patients and survivors need not only clinically competent professionals, but professionals who provide caring interactions with compassion.